Transformasi Spiritual di Desa Lekopancing: Peran Strategis KKN dalam Menghidupkan Kesadaran Keagamaan Masyarakat: Spiritual Transformation in Lekopancing Village: The Strategic Role of Community Service Programs in Revitalizing Religious Awareness - Nabilah Al Azizah; Novira, Nuraeni (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
The Community Service Program (KKN) conducted by the seventh cohort of STIBA Makassar students in Lekopancing Village, Maros Regency, exemplifies a tangible implementation of the community service pillar within the Tri Dharma of Higher Education. This initiative aims to empower the village community through a systematic and needs-based approach. The program's execution began with problem mapping and the identification of community needs using SOAR (Strengths, Opportunities, Aspirations, and Results) analysis. Based on this analysis, a series of work programs were developed to address the specific needs of the local community. The programs implemented included Qur'an Education (TK/TPA), DIROSA, School Teaching Programs, Weekend Tahfidz, Taklim Muslimah, Ifthar Distribution (Breaking Fast), 20-Day Memorization Daura, Funeral Management Training, Pious Children Festival, Taklim Sakinah, Aurat Covering Movement, and Sunnah Cupping Therapy. Each program was carried out using a participatory approach, actively involving the community, and has shown initial outcomes aligned with the primary objectives of the KKN. Preliminary evaluations indicate that these programs have not only been successfully implemented but have also had a positive impact on enhancing the social and religious quality of life in Lekopancing Village.